The Internet as Complex Networks: Understanding Its Structure and Its Dynamical Properties - Ferry Astika Saputra (Fakultas MIPA Universitas Brawijaya, 2013)
Structures and properties of networks have been attracting research interests in various research fields. The Internet has been investigated as complex networks. The structure of the Internet has been reported to be scale-free. Namely, the degree distribution at a router level obeys a power law. The packet flow in the Internet also has been reported to obey a power law. In this paper, models of networks are investigated theoretically and with simulations. The dynamical properties of those networks are also discussed.